2005
DOI: 10.1029/2005gl023199
|View full text |Cite
|
Sign up to set email alerts
|

Absence of isotope exchange in the reaction of N2O + O(1D) and the global Δ17O budget of nitrous oxide

Abstract: Yung et al. (2004) suggested that N2O exchanges isotopes with O(1 D), analogous to CO2, which would represent an additional contribution to the 17O isotope anomaly of atmospheric N2O. Here we demonstrate by isotope measurements of N2O remaining after partial conversion with O(1 D) that this isotope exchange most likely proceeds a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
3
23
0
Order By: Relevance
“…The anomaly is on the order of 50%. To explain the observed 1% oxygen anomaly in N 2 O, the atmospheric source of N 2 O needs to be about 2% of the total source, i.e., a column production of N 2 O $5 Â 10 7 molecules cm À2 s À1 or 0.4 TgN/ year, consistent with the suggestion by Kaiser and Röckmann [2005].…”
Section: Two-dimensional Simulationsupporting
confidence: 69%
See 3 more Smart Citations
“…The anomaly is on the order of 50%. To explain the observed 1% oxygen anomaly in N 2 O, the atmospheric source of N 2 O needs to be about 2% of the total source, i.e., a column production of N 2 O $5 Â 10 7 molecules cm À2 s À1 or 0.4 TgN/ year, consistent with the suggestion by Kaiser and Röckmann [2005].…”
Section: Two-dimensional Simulationsupporting
confidence: 69%
“…These processes have been summarized and discussed by McLinden et al [2003] and Kaiser and Röckmann [2005]. In addition to the aforementioned proposals that generate nonzero D 17 O in the atmosphere, it has also been suggested that microbial production of N 2 O in the biosphere [Michalski et al, 2003;Kaiser et al, 2004;Kaiser and Röckmann, 2005] could contribute the observed oxygen anomaly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the atmospheric detection of an Earth-like amount of nitrous oxide (N 2 O) for an Earth-like planet orbiting a sunlike star would constitute a biosignature because according to current knowledge, such a signal could not be produced by anything other than microbes. In other words, the known atmospheric abiotic sources (for an overview see, e.g., Kaiser and Röckmann 2005) for this gas are much too slow to "mimic" life in such a case.…”
Section: Overviewmentioning
confidence: 99%